Visual study for ceramic material (Journal of the College of Basic Education, 2022)
Six samples of production material were prepared by mixing certain proportions of raw materials of Iraqi origin (kaolin, flint and potassium feldspar) and studying the change in the weight ratio of potassium feldspar included in the composition of samples of the ceramic material prepared from those components in Basra, and establishing addition percentages for potassium feldspar (0%) 10%, 20%, 30%, 40%,